Analisis Bibliometrik Pembelajaran Berbasis Science, Technology, Engineering, and, Mathematics (STEM) pada Tingkat SMP dan MTs Menggunakan Google Scholar Database - Barus, Carolina Sri Athena; Jaya, Gede Wiratma (Jurnal Literasi Pendidikan Fisika (JLPF), 2025)
The analysis of the development of STEM implementation in Junior High Schools (SMP) and Madrasah Tsanawiah (MTs) is still limited, making it unknown how widely STEM has been applied. This study aims to analyze the progress of STEM implementation in SMP and MTs from 2011 to 2024 using a bibliometric analysis. This analysis utilizes the Publish or Perish (PoP) and VOSviewer software. The research results show a total of 91 articles on the topic of STEM from 2011–2024, as retrieved using the Publish or Perish (PoP) software. The implementation of STEM is predominantly carried out in SMP, focusing more on research activities. Furthermore, Natural Science subjects are more frequently applied in STEM learning. The application of STEM is more prevalent in Western Indonesia. Visualization using the VOSviewer software generated a keyword co-occurrence network map consisting of five clusters and 26 keywords. The overlay visualization indicates several keywords that have the potential to be used as research topics. The density visualization reveals that the keyword STEM is the most frequently occurring topic in the articles. It is anticipated that the findings of the bibliometric analysis will assist researchers in developing the implementation of STEM in SMP and MTs.